2016
DOI: 10.1186/s13098-016-0175-z
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell death is decreased in women with gestational diabetes mellitus

Abstract: BackgroundGestational diabetes mellitus (GDM) affects approximately 7–17 % of all pregnancies and has been recognized as a significant risk factor to neonatal and maternal health. Postpartum, GDM significantly increases the likelihood of developing type 2 diabetes (T2D). While it is well established that insulin resistance and impaired β-cell function contribute to GDM development, the role of active β-cell loss remains unknown. Differentially methylated circulating free DNA (cfDNA) is a minimally invasive bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
(41 reference statements)
2
7
0
1
Order By: Relevance
“…We did not observe any increase in unmethylated insulin cfDNA copies in women who progressed to T2DM during the study. This is in line with the gestational islet β -cell death measurements made by Kenna et al [24], suggesting that there is no islet β -cell death during pregnancy or immediately postpartum but that the overall effect of GDM-related stressors affects nonislet tissues that possibly induce a series of inflammatory events resulting in reduced β -cell function and progression to T2DM later in life.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We did not observe any increase in unmethylated insulin cfDNA copies in women who progressed to T2DM during the study. This is in line with the gestational islet β -cell death measurements made by Kenna et al [24], suggesting that there is no islet β -cell death during pregnancy or immediately postpartum but that the overall effect of GDM-related stressors affects nonislet tissues that possibly induce a series of inflammatory events resulting in reduced β -cell function and progression to T2DM later in life.…”
Section: Discussionsupporting
confidence: 89%
“…This is the first report analyzing postpartum insulin cfDNA in a longitudinal study cohort of women with GDM ( n = 97). In an earlier cross-sectional study, 22 women with GDM were compared with 14 non-GDM pregnant women with an aim to assess the death of pancreatic β -cell (increased unmethylated insulin cfDNA) in the women with GDM [24]. These investigators did not observe any increased islet β -cell death in mothers with GDM compared to those without GDM.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that with technological advances, more target genes of interest can be explored and readily combined into panels to optimize the sensitivity and specificity of these assays. Another recent study reported a negative relation between the onset of gestational diabetes mellitus (GDM) and β cell loss by using the detection of unmethylated INS DNA [ 31 ]. Interestingly, the levels of unmethylated INS DNA were significantly decreased in women with GDM comparing to women with normal pregnancy, women at postpartum, and non-pregnant women [ 31 ].…”
Section: Future Prospectsmentioning
confidence: 99%
“…Another recent study reported a negative relation between the onset of gestational diabetes mellitus (GDM) and β cell loss by using the detection of unmethylated INS DNA [ 31 ]. Interestingly, the levels of unmethylated INS DNA were significantly decreased in women with GDM comparing to women with normal pregnancy, women at postpartum, and non-pregnant women [ 31 ]. The study told us that the detection of unmethylated INS DNA may provide more detailed information about the natural history and heterogeneity of T1D, which is crucial to illustrate the etiology of T1D [ 32 ].…”
Section: Future Prospectsmentioning
confidence: 99%
“…6 A significant risk factor for GDM has been documented as maternal health, macrosomia and cesarean delivery. 7 Born neonates to GDM mother will have risk of low blood glucose other complications such as jaundice, pre-eclampsia, polycythemia and respiratory related syndromes. 8 All types of diabetes such as T1DM, T2DM, GDM and specific types of diabetes due to other causes has genetic com--ponent.…”
Section: Introductionmentioning
confidence: 99%